Privatization Public Policy: A Look At The Experience of managing schools from San Luis - Feldfeber, Myriam; Jaimovich, Analía; Saforcada, Fernanda (Education Policy Analysis Archives, 2004)
The educational reform that took place in Argentina during the ´90s should be analyzed in the context of a broader reform process implemented in the whole of Latin America during that period, aimed at reforming the State and introducing deregulation, decentralization and privatization policies. During this process, the role that the Sate traditionally held in education is redefined, and the responsibility of guaranteeing the right to education is transferred form the State to the families and the schools. These transformations redefine the public character of public education, introduce new meanings in the debates and views about when something should be considered public or not in the field of education and foster the creation of a non- state public space which could be placed between the State and the market. This paper aims at analyzing the project “Escuelas 2001” which seeks to implement charter schools in San Luis, Argentina. The analysis is based on a two-fold approach: on the one hand, it takes into consideration the logic underlying the design and implementation of this policy; on the other hand, it focuses on the actors’ views about education, the State and public institutions.